PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN NON MEDIS RUMAH SAKIT ISLAM SITI KHODIJAH PALEMBANG - Tini, Mar (Jurnal Manajemen, 2016)
This study aimed to analyze the influence of the working environment and working discipline on employee performance. The population in this study is employee of Islamic Hospital Siti Khodijah Non-Medical Section with propotional random sampling method. The data was analyzed by using multiple regression analysis. The results of this studi indicated the working environment and working discipline simultaneous effect on the performance of the F test obtained by F count (75.522) > F table (3.13) to test the significant and got the (P value) = 0.000 <0.05.The result also showed the working environment and working discipline significant effect partially by t test result working environment for 5,035 t > t table 1.66724 and significant 0,000 < 0.05. eventhough working discipline of 3.482 t count> t table 1.66724 and significant 0,001 < 0.05. And working environment dominant influence on the achievement by the coefficient value of 0.592. Based on the results of research showed the working environment and working discipline has significant influence on the performance of that hypothesis is accepted.